Analysis of the influence of brand experience, customer engagement on brand trust through brand attachment as an intervening variable in Gojek users in Padang City - Wahyu Dionaldo; Yunita Engriani (Universitas Negeri Padang, 2021)
The purpose of this study is to analyze: (1) The Influence of Brand Experience on Brand Trust. (2) The Effect of Customer Engagement on Brand Trust. (3) Influence of Brand Attachment on Brand Trust. (4) Influence of Brand Experience on Brand Trust through Brand Attachment as Intervening Variable. (5) Influence of Customer Engagement on Brand Trust through Brand Attachment as Intervening Variable. The population in this study is the user of the Gojek app service in Padang City. The sampling technique in this study is Purposive Sampling with a sample number of 250 respondents in 2021. Analysis in this study using SmartPLS 3.0. The results of this study are: (1) Brand Experience had no significant and negative effect on Brand Trust. (2) Customer Engagement has a significant and positive effect on brand trust. (3) Brand Attachment has no significant and negative effect on brand trust. (4) Brand Experience has no significant and negative effect on Brand Trust through Brand Attachment as an intervening variable. (5) Customer Engagement has no significant and negative effect on Brand Trust through Brand Attachment as an intervening variable